Smart light powered soft robots with multicolour response - Lee, Hern Yi (Nanyang Technological University, 2022)
Soft robots are an interesting new technology that is very different from traditional mechanical robots. The designs and movements are closely related and inspired by living things, and this allows it to function very closely similar to a living thing. This project will review the various design of a soft robot, from its inspirations to the calculations and measurements, and how the robots will be tested for it response to light and magnetic stimulus, either physically or by simulation. A soft robot is designed, fabricated and the prototype will be tested.